The local immune response of mice after Helicobacter suis infection: strain differences and distinction with Helicobacter pylori - Flahou, Bram (BioMed Central, 2012)
Helicobacter (H.) suis colonizes the stomach of pigs and is the most prevalent gastric non-H. pylori Helicobacter species in humans. Limited information is available on host immune responses after infection with this agent and it is unknown if variation in virulence exists between different H. suis strains. Therefore, BALB/c and C57BL/6 mice were used to compare colonization ability and gene expression of various inflammatory cytokines, as determined by real-time PCR, after experimental infection with 9 different H. suis strains. All strains were able to persist in the stomach of mice, but the number of colonizing bacteria at 59 days post inoculation was higher in stomachs of C57BL/6 mice compared to BALB/c mice. All H. suis strains caused an upregulation of interleukin (IL)-17, which was more pronounced in BALB/c mice. This upregulation was inversely correlated with the number of colonizing bacteria. Most strains also caused an upregulation of regulatory IL-10, positively correlating with colonization in BALB/c mice. Only in C57BL/6 mice, upregulation of IL-1β was observed. Increased levels of IFN-γ mRNA were never detected, whereas most H. suis strains caused an upregulation of the Th2 signature cytokine IL-4, mainly in BALB/c mice. In conclusion, the genetic background of the murine strain has a clear impact on the colonization ability of different H. suis strains and the immune response they evoke. A predominant Th17 response was observed, accompanied by a mild Th2 response, which is different from the Th17/Th1 response evoked by H. pylori infection.